TINJAUAN TENTANG KEPUASAN KERJA KARYAWAN PADA PT. GUANTA SAMBA KEBUN PENGADAAN ESTATE KECAMATAN KARANGAN KABUPATEN KUTAI TIMUR - Inggal Anggriani (ADMINISTRASI PUBLIK, 2018)
of research on data analysis for job characteristics occupy the dominant role where in the calculation of hypothesis through t test is obtained t arithmetic for job characteristics variable of 2.621 where t arithmetic greater than t table (2.621> 1.997), from the results of regression coefficient of job satisfaction employees in job characteristics variable (X1) of 0.337, and the magnitude of the dominance of job characteristics to employee job satisfaction is 0.376.The calculation results simultaneously show the results of the calculation This research is based on employee work satisfaction of PT. Guanta Samba Pengandan Sub-District of Karangan, East Kutai Regency, which is expected to fulfill the needs of its employees.The purpose of this study is to determine employee job satisfaction at PT. Guanta Samba with indicator of the character of the work of achievement motivation, opportunity to grow, responsibility and reward. The type of research or explanation used is descriptive kuanlitatif used to analyze the relationship between research variables. Types of data used are kusioner, observation, interview, and documentation.From the results of the hypothesis test F obtained F arithmetic with a significance level of 0.05 for 4780 and F table value of 2.356 so Ho is rejected and Ha accepted. While the summary model test results obtained r2 number of 0.669 this means that 66.9% and 33.1% influenced by other factors.